Sutureless microvascular anastomosis with the aid of heparin loaded poloxamer 407. Issue 2 (February 2017) - Özer, Fırat; Nişancı, Mustafa; Taş, Çetin; Rajadas, Jayakumar; Alhan, Doğan; Bozkurt, Yalçın; Günal, Armağan; Demirtaş, Serdar; Işık, Selçuk
Summary: Background: Anastomosis with tissue adhesives is an alternative method for conventional anastomosis. However, this method has several technical challenges. It requires the use of suture to prevent leakage into lumen and precise application onto all surfaces of the anastomosis site. To solve these problems, poloxamer 407 (P 407) was previously used as a stent. In this study, we made heparinized P 407 (h-P 407) as a new formula. We aimed to successfully use h-P 407 as a stent in sutureless anastomosis in a rat abdominal aorta model. Methods: Sixty Sprague–Dawley rats were used. In the first group, end-to-end anastomoses were performed with suture; in the second and third groups, sutureless anastomoses were performed with 2-octyl cyanoacrylate. As an intraluminal stent, P 407 was used in the second group, and h-P 407 was used in the third group. Anastomosis time was measured. Lumen width, intimal hyperplasia, and foreign body reaction were assessed histologically. Velocity flow rates and vessel diameters were measured radiologically. Burst strength was measured, and the results were statistically evaluated. Results: Sutureless anastomosis was more rapid than conventional anastomosis. Lumen width was narrower in the suture group. İnflammation and foreign body reaction were more severe in the suture group. There was no radiologic and biomechanical difference between the groups. We found that intimal hyperplasia was less in h-P 407 than in P 407. Conclusion: h-P407 can be successfully used as an intraluminal stent for sutureless microvascular anastomosis with tissue adhesives.